1976
DOI: 10.1128/iai.13.2.619-626.1976
|View full text |Cite
|
Sign up to set email alerts
|

Activity of two Streptococcus mutans bacteriocins in the presence of saliva, levan, and dextran

Abstract: The extracellular dextrans produced from sucrose by Streptococcus mutans strains BHT and GS-5 did not prevent the synthesis or release of active bacteriocins by these two strains. In addition, several streptococci that were genetically sensitive to these bacteriocins, and that could synthesize a variety of extracellular dextrans and levans from sucrose, remained phenotypically sensitive when grown in the presence of sucrose. Bacteriocin activity was not altered by treatment with high-molecular-weight dextran o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…mutans were producing a bacteriocin, the insoluble EPS might render Strep. mitior less susceptible to its action (Rogers 1974), although conflicting evidence has been obtained on this point (Delisle 1976). Another effect of the insoluble EPS may be to provide protection against inhibitory acid (Donoghue & Newman 1976), thus increasing the proportion of Strep.…”
Section: Discussionmentioning
confidence: 99%
“…mutans were producing a bacteriocin, the insoluble EPS might render Strep. mitior less susceptible to its action (Rogers 1974), although conflicting evidence has been obtained on this point (Delisle 1976). Another effect of the insoluble EPS may be to provide protection against inhibitory acid (Donoghue & Newman 1976), thus increasing the proportion of Strep.…”
Section: Discussionmentioning
confidence: 99%
“…Since bacteriocins are proteins and thus potentially susceptible to the action of proteases, they would be inactivated rapidly in situ by plaque proteases (20). However, according to others (6,12), many bacteriocin-like substances, although sensitive to trypsin, are only slightly affected by plaque proteases. A third objection was raised as a result of the observation that protection against bacteriocin action was induced in sensitive oral streptococci on growth in media containing sucrose (27,31), presumably as a consequence of the diffusion barrier provided by the extracellular polysaccharides formed.…”
Section: Discussionmentioning
confidence: 99%
“…FIG. 6. Total number of viable cells in preestablished S. mutans OMZ61s plaque alone (0) and after incubation with S. sanguis P3A3 added at the time indicated by the arrow (a).…”
Section: Discussionmentioning
confidence: 99%
“…Kelstrup and Gibbons (10) also reported that saliva inactivated streptococcal bacteriocins, and they attributed this inactivation to proteolytic enzymes. In contrast, bacteriocins produced by S. mutans BHT and GS-5 were unaffected by human saliva (7).…”
Section: Discussionmentioning
confidence: 80%